2017
DOI: 10.1186/s13640-016-0161-2
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation method based on multiobjective optimization for very high spatial resolution satellite images

Abstract: In this paper, a new multicriterion segmentation method has been proposed to be applied to satellite image of very high spatial resolution (VHSR). It is consisted of the following process: For each region of the grayscale image, a center of gravity has been calculated and it has been also selected a threshold for its histogram. According to a certain criteria, this approach has been based on the separation of the different classes of grayscale in an optimal way. The proposed approach has been tested on synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Figure 3 presents the segmented results for synthetic images. In addition, the table 2 illustrate the results obtained by our method and their challenging with the method [5]; it authenticates that the good results obtained by our developed method.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…Figure 3 presents the segmented results for synthetic images. In addition, the table 2 illustrate the results obtained by our method and their challenging with the method [5]; it authenticates that the good results obtained by our developed method.…”
Section: Resultssupporting
confidence: 77%
“…To study the influence of small regions, the first image we preferred contained a texture. We observed that the values of the inter-region, intra-inter-region and MSE criteria of our proposed method are lower than those provided by the method [5], and the intra-region criterion values are superior. The same findings obtained when processing other synthetic images having different morphological properties.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations